Cost-effectiveness of narlaprevir in the chronic hepatitis C (genotype 1) therapy in treatment-naïve patients and relapsers - D. A. Gusev (Žurnal Infektologii, 2016)
In the treatment of chronic hepatitis C (CHC) protease inhibitors (PI) are actively used. The aim of this analysis was to evaluate the cost-effectiveness of narlaprevir and simeprevir in the CHC (genotype 1) therapy in treatment-naïve patients and relapsers.Material and methods. Analysis of the cost-effectiveness of simeprevir and narlaprevir was conducted from the perspective of the health care system based on QUEST-1, QUEST-2, ASPIRE and PIONEER clinical trials. The relative risk of achieving SVR 24 compared to the peg-INF + RBV therapy was used in the model. Treatment discontinuation in patients receiving narlaprevir assumed in the absence of a SVR after 12 weeks and in patients receiving simeprevir in the SVR absence after 4 weeks. The cost of narlaprevir was calculated on the basis of estimated registration price in case of EDL inclusion, including VAT. Costs of other antiviral drugs were in line with the results of 2016 average auctions prices.Results. In the base case costs on antiviral drugs with narlaprevir as therapy are lower compared with simeprevir by 37,3 % (542,0 and 864,6 thousand rur, respectively), and the cost per patient with SVR 24 by 34,5%. In patients after relapse costs on antiviral drugs with narlaprevir as first-line therapy will decrease compared with simeprevir by 22,8% (542,0 and 702,5 thousand rur, respectively), and the cost per patient with SVR 24 by 41,3%. The sensitivity analysis demonstrated a high reliability of obtained results.Conclusions. With comparable clinical efficacy and tolerability of narlaprevir and simeprevir both in treatment-naïve patients and patients with relapse after therapy, which included pegylated interferon and ribavirin, narlaprevir reduces the burden on the budget.